A contribuição marxista para o estudo das relações internacionais - Vigevani, Tullo [UNESP]; Martins, Aline Regina Alves; Miklos, Manoela [UNESP]; Rodrigues, Priscila [UNESP] (FapUNIFESP (SciELO), 2011)
The article examines the marxist contribution to the study of international relations stressing the historical dimension in the social groups and political economy as a fundamental variable. Thus, marxism provides resources to a comprehensive analysis of international relations, deconstructing the concept of state as is understood by the dominant theories in the area.
The marxist contribuition to the study of internactional relations
Keywords: Critical theory; International relations; International relations theory; Marxism